Transformasi Layanan Kemanusiaan Berbasis Agama: Studi Komparasi Lembaga Zakat Korporat YBM BRILiaN, BSI Maslahat, dan YBM PLN - Dwi Iqbal Noviawan; Banu Muhammad Haidlir; Sari Viciawati Machdum (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
This study examines the organizational transformation of three corporate-based zakat institutions—YBM BRILiaN, BSI Maslahat, and YBM PLN—by positioning regulatory pressures, demands for professionalism, and rapid digital advancement as the primary drivers of change. Wamsley and Zald’s political–economic perspective is used to explain how external forces—particularly state regulation and the policies of parent corporations—influence authority structures, program direction, and institutional accountability. Meanwhile, Kettner’s framework on organizational change provides the basis for analyzing internal dynamics, including human resource development, structural reorganization, and adjustments in governance practices. Employing a qualitative comparative approach, the study utilizes in-depth interviews and document analysis to trace the patterns of transformation across the three institutions. The findings reveal differentiated strategies: YBM BRILiaN prioritizes structural efficiency, amil cadre development, and consolidation of digital systems; BSI Maslahat focuses on post-merger cultural harmonization, SOP unification, and integration of data and reporting mechanisms; while YBM PLN implements nationwide KPI-based standardization, full digitalization of reporting processes, and strengthened regional volunteer networks. Despite these divergent pathways, the institutions exhibit convergence in several areas, including the professionalization of human resources, reinforcement of audit and control mechanisms, and the use of technology as a key instrument of public accountability. These results demonstrate that corporate-based zakat institutions are not only adapting to external pressures but also negotiating religious values alongside managerial practices to strengthen legitimacy and ensure the sustainability of faith-based social services.